Resident and Visitor Perceptions of Island Tourism: Green Sea Turtle Ecotourism in Penghu Archipelago, Taiwan - Yu-Long Chao; Shang-Yu Chao (Island Studies Journal, 2017)
This study compares residents and visitors on the island of Wang-An in Penghu archipelago (Taiwan) in terms of four variables (ecotourism perception, environmental attitude, ecotourism behavior, local environmental knowledge). Results show that island visitors are positioned closer to the deep end of a shallow-deep spectrum on a few ecotourism characteristics such as stronger environmental commitment, smaller groups, and more personal experience. With a fuzzy cluster analysis reducing the four variables to two dimensions (ecotourism literacy, environmental familiarity and concern), the two clusters of island residents and visitors are found to overlap greatly with a noticeable divergence in the dimension of environmental familiarity and concern as a result of residents’ better local environmental knowledge. Residents express greater approval of economic development on some items of the environmental attitude subscale. It is recommended that visitors have longer tours that increase interaction with residents to learn more about the local environment while serving as educators of ecotourism.